Analisis Perbedaan Nilai Hasil Belajar antara Siswa Madrasah Aliyah yang Bermain dan Tidak Bermain Mobile Gaming - Fuadiy, Moch. Rizal; Qomarudin (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
This research aims to examine whether there is a difference in learning outcomes between two groups of Madrasah Aliyah students. The first group consists of students not involved in Mobile Gaming, while the second group comprises students actively engaged in Mobile Gaming. The research method employed is quantitative research, with data collection conducted through a survey of 302 students in the twelfth grade of Madrasah Aliyah Negeri (MAN) 1 Tulungagung. The survey results indicate that 60.59%, or 183 students, belong to the group that does not play Mobile Gaming, while 39.4%, or 119 students, are Mobile Gaming players. The average learning outcomes of both student groups were analyzed using the Mann-Whitney U test to assess the differences between them. The Mann-Whitney U test results show that the learning outcomes of students in the group not playing Mobile Gaming are higher, although the difference is not significant (median=92.18), compared to the group of students playing Mobile Gaming (median=91.75), U=13132.5, p=0.002. The Hodges-Lehmann estimate of 0.5 supports the Mann-Whitney U test results, indicating a small median difference between the two student groups. Despite the observed difference, the small effect size is indicated by the rank biserial correlation value ra=0.206. Therefore, it can be concluded that there is no significant difference in learning outcomes between the two student groups, those who play Mobile Gaming and those who do not.